1988
DOI: 10.1029/ja093ia09p09555
|View full text |Cite
|
Sign up to set email alerts
|

The role of interplanetary shocks in the longitude distribution of solar energetic particles

Abstract: A study of solar proton events with well‐identified sources has been carried out using data from Goddard particle experiments on IMPs 4, 5, 7, and 8 and ISEE 3. The experiments cover the energy range from about 1 to 300 MeV. The 235 events of our study represent approximately 70% of all increases above 10−3 particles cm−2 sr−1 s−1 MeVminus;1 at energies > 20 MeV detected in a 19.7‐year period commencing mid‐May 1967. It is shown that intensity‐time profiles of solar proton events display an organization with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
316
2
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(339 citation statements)
references
References 29 publications
18
316
2
3
Order By: Relevance
“…A key issue that is not well known is the primary acceleration region along the CME shock where most of highenergy particles are produced. While several studies have shown that the large gradual SEP events can be understood under the assumption that the shock nose is the main source of energetic particles (e.g., Cane et al 1988;Reames et al 1997;Reames 1999), some other studies have suggested that the shock flank can provide the majority of energetic particles (e.g., Kahler 2016). We note here that the role of magnetic field configuration is of great importance for determining the primary acceleration region.…”
Section: Introductionmentioning
confidence: 90%
“…A key issue that is not well known is the primary acceleration region along the CME shock where most of highenergy particles are produced. While several studies have shown that the large gradual SEP events can be understood under the assumption that the shock nose is the main source of energetic particles (e.g., Cane et al 1988;Reames et al 1997;Reames 1999), some other studies have suggested that the shock flank can provide the majority of energetic particles (e.g., Kahler 2016). We note here that the role of magnetic field configuration is of great importance for determining the primary acceleration region.…”
Section: Introductionmentioning
confidence: 90%
“…This time delay (∆ t) can be up to about 127 5 days at 1 AU (Cane et al, 1988). The SEP intensity peaks impulsively 128 soon after the onset since connection to the shock region has a short duration 129 and/or because the observer gets gradually connected to weaker parts of the 130 shock.…”
mentioning
confidence: 99%
“…and Cane et al (1988), provides useful insights on the different ways SEPs 120 may reach an observer, despite being based on observations at 1 AU.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Cane et al (1988), an abrupt decrease in the particle¯uxes is expected to be observed as the spacecraft enters the CME. However, on the contrary, in March 1991, an enhancement is observed at the onset of the ®rst CME and no variation in the particle¯ux is observed for the second CME.…”
Section: Discussionmentioning
confidence: 99%